A Design Principle for Polar Assemblies with C3‐Sym Bowl‐Shaped π‐Conjugated Molecules. Issue 6 (10th December 2020) - Zhang, Cheng; Guo, Yuan; He, Dan; Komiya, Jouji; Watanabe, Go; Ogaki, Takuya; Wang, Chengyuan; Nihonyanagi, Atsuko; Inuzuka, Hiroyuki; Gong, Hao; Yi, Yuanping; Takimiya, Kazuo; et al.
Abstract: Polar materials attract wide research interest due to their unique properties, such as ferroelectricity and the bulk photovoltaic effect (BPVE), which are not accessible with nonpolar materials. However, in general, rationally designing polar materials is difficult because nonpolar materials are more favorable in terms of dipole‐dipole interactions. Here, we report a rational strategy to form polar assemblies with bowl‐shaped π‐conjugated molecules and a molecular design principle for this strategy. We synthesized and thoroughly characterized 12 single crystals with the help of various theoretical calculations. Furthermore, we demonstrated that it can be possible to predict whether polar assemblies become more favorable or not by estimating their lattice energies. We believe that this study contributes to the development of organic polar materials and their related studies. Abstract : Polar materials attract wide research interests because of their unique properties, such as ferroelectricity and the bulk photovoltaic effect. However, polar organic assemblies are limited due to the lack of rational synthetic strategies. Here, we report the first rational strategy to form polar organic crystals based on bowl‐shaped π‐conjugated molecules.